2011
DOI: 10.3727/108354211x13149079788936
|View full text |Cite
|
Sign up to set email alerts
|

Wine Tourism Experience and Consumer Behavior: The Case of Sicily

Abstract: Wine tourist behavior-based research is essential to the development of wine tourism and to help wine producers to manage wine tourist demand. Wine tourism has increased substantially in the last decade throughout the whole Italian peninsula. Sicily, which represents an area becoming ever more a center of attraction concerning wine tourism, so far lacks research regarding winery visits and wine tourists in general. This article focuses on the wine tourism experience and consumer behavior, aiming to explore at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 29 publications
4
46
0
1
Order By: Relevance
“…Wine tourism also provides a reasonably low-cost distribution channel for the sale of wine and associated products directly to consumers (Getz & Brown, 2006, p. 147). By adding complementary visitor-oriented services, wine businesses build brand loyalty, improve consumer awareness and knowledge, create a positive image of the wine product, and develop strong consumer relationships through planned on-site experiences (Asero & Patti, 2011;Bruwer & Alant, 2009;Yan, Morrison, Cai, & Linton, 2008). Researchers focusing on this area have suggested that many of the issues related to consumer interest in wine tourism have yet to be revealed (Bruwer & Lesschaeve, 2012) and warrant additional research on the wine tourism consumer base (Getz & Brown, 2006;Hall et al, 2000;Yan et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…Wine tourism also provides a reasonably low-cost distribution channel for the sale of wine and associated products directly to consumers (Getz & Brown, 2006, p. 147). By adding complementary visitor-oriented services, wine businesses build brand loyalty, improve consumer awareness and knowledge, create a positive image of the wine product, and develop strong consumer relationships through planned on-site experiences (Asero & Patti, 2011;Bruwer & Alant, 2009;Yan, Morrison, Cai, & Linton, 2008). Researchers focusing on this area have suggested that many of the issues related to consumer interest in wine tourism have yet to be revealed (Bruwer & Lesschaeve, 2012) and warrant additional research on the wine tourism consumer base (Getz & Brown, 2006;Hall et al, 2000;Yan et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…Although there is no single theory that defines tourist experience, the hedonic view of tourism consumption underlines the relevance of its theoretical framework to understanding the experiences sought by tourists. This prompted Quadri‐Felitti and Fiore (, p.5) to conclude that this “affords a logical connection to wine tourism with its emphasis on senses, emotions, and enjoyment of pastoral settings.” Few wine tourism studies have focused on the total experience aspect, in other words, what reasons other than the obvious “to taste” and “to buy wine” actually motivated them to visit (Asero & Patti, ; Chen, Bruwer, Cohen, & Goodman, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In tune with the various developments taking place regarding wine tourism development in Europe, academic research has also grown significantly (Asero and Patti, ; Alonso and Liu, ; Gómez and Molina, ; López‐Guzmán et al ., ; Marzo‐Navarro and Pedraja Iglesias, 2012). A central theme in many wine tourism studies has been the various socio‐economic benefits that might be achieved through wine tourism development (Beverland, ; Getz, ; Hall et al ., ; Mitchell and Hall, ).…”
Section: Introductionmentioning
confidence: 99%